PENGARUH DISIPLIN TERHADAP KINERJA DENGAN VARIABEL EFIKASI DAN MOTIVASI EKSTERNAL SEBAGAI EKSOGEN - Herlin Amelia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The growth of the hotel industry in the Cilegon city continues to increase, this is indicated by the establishment of many new hotel buildings. However, things got even more difficult, when there was a pandemic. In a difficult time like this, the obstacle is not only competition, but the decline in public interest in the tourism industry is a very heavy blow. Therefore, companies are required to improve service quality, one of which is through improving employee performance. In fact, this study intends to examine how the role of human resource quality on hotel performance, even during a pandemic, is able to retain visitors. To prove the correctness of the research, a quantitative method is determined as the basis for research, and path analysis as an analytical tool. The research object is Hotel Sari Kuring Indah, Cilegon City, the research subjects are employees, simple random sampling technique, and the number of respondents is 103. The results confirm that in the hotel industry employee performance in the form of service greatly impacts the interest of hotel visitors. In addition, the performance of hotel employees is greatly influenced by the level of discipline. However, the emergence of disciplined behavior will be formed if employees have high morale, both internally and externally.